2013
DOI: 10.3389/fncom.2013.00067
|View full text |Cite
|
Sign up to set email alerts
|

Set-size effects for sampled shapes: experiments and model

Abstract: The location of imperfections or heterogeneities in shapes and contours often correlates with points of interest in a visual scene. Investigating the detection of such heterogeneities provides clues as to the mechanisms processing simple shapes and contours. We determined set-size effects (e.g., sensitivity to single target detection as distractor number increases) for sampled contours to investigate how the visual system combines information across space. Stimuli were shapes sampled by oriented Gabor patches:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 64 publications
(138 reference statements)
1
13
0
Order By: Relevance
“…For a frequency of RF5, the critical amplitude A crit = 0.038. Both values are close to the data points where coherence thresholds relative to a circle start to increase (ω ≤ 4; A ≤ 0.05; Figure 3), suggesting that the transition from convex to concave may be an important factor in the processing of RF shapes (Kempgens et al, 2013). …”
Section: Discussionsupporting
confidence: 76%
“…For a frequency of RF5, the critical amplitude A crit = 0.038. Both values are close to the data points where coherence thresholds relative to a circle start to increase (ω ≤ 4; A ≤ 0.05; Figure 3), suggesting that the transition from convex to concave may be an important factor in the processing of RF shapes (Kempgens et al, 2013). …”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, similar to the current results, the effect of interelement spacing on contour grouping was the same in younger and older subjects (Hadad, 2012;Roudaia et al, 2013), even though overall ability to detect and discriminate contours in noise declines with aging (Del Viva & Agostini, 2007;Roudaia et al, 2011Roudaia et al, , 2013. Although Day and Loffler (2009) speculated that the shape illusion is generated by integration by a global pooling mechanism, as opposed to local contour integration mechanisms thought to underlie detection of elongated contours in noise (e.g., Field, Hayes, & Hess, 1993), there is growing evidence suggesting that global shape mechanisms do not operate directly on individual contour elements, but instead pool information from intermediate-stage mechanisms that integrate local orientation information to encode curved contour segments and inflection points (e.g., Bell et al, 2011;Bell, Hancock, Kingdom, & Peirce, 2010;Kempgens et al, 2013;Schmidtmann et al, 2012). To the extent that there may be shared, overlapping mechanisms that contribute to performance in different tasks that involve the integration of orientation information in sampled contours, the current results are consistent with previous studies (Hadad, 2012;McKendrick et al, 2010;Roudaia et al, 2013) in finding no differential effect of interelement spacing on performance with aging.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have shown that the inputs to the global pooling stage are themselves outputs of intermediate stage curvature detectors that integrate local orientation information to encode curvature and inflection points along the contour (Bell et al, , 2010(Bell et al, , 2011. A biologicallyplausible model developed by Kempgens et al (2013), based on an earlier model by Poirier and Wilson (2006), consists of five stages: In the first three stages, local contour information, the size and center of the shape are determined and, in the fourth stage, multiple local curvature units integrate information from local orientation channels in a nonlinear fashion, and outputs of one or more of these curvature units are combined with the earlier stages of the model to represent the curvature signals in relation to the center of the shape. In the final stage, a global mechanism pools the inputs of the various arc units from the fourth stage and a population code of these convexities and concavities in different locations around the shape combine to represent different shape types.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these behavioral results, models have been devised for shape processing that incorporate a population code strategy (Kempgens, Loffler, & Orbach, 2013;Poirier & Wilson, 2006;Wilson & Wilkinson, 2015). This follows cell recordings from V4, which have been shown to be consistent with a population code for complex curved shapes (Pasupathy & Connor, 2001.…”
Section: Population Code For Shape Processingmentioning
confidence: 99%
“…One model (Kempgens et al, 2013) arose from a psychophysical investigation into the ability to detect local changes in sampled RF contours. Observers were required to detect a deviation in orientation of one element from tangential to the sampled shape.…”
Section: Population Code For Shape Processingmentioning
confidence: 99%